2019
DOI: 10.4103/1673-5374.245334
|View full text |Cite
|
Sign up to set email alerts
|

The pig as a preclinical traumatic brain injury model: current models, functional outcome measures, and translational detection strategies

Abstract: Traumatic brain injury (TBI) is a major contributor of long-term disability and a leading cause of death worldwide. A series of secondary injury cascades can contribute to cell death, tissue loss, and ultimately to the development of functional impairments. However, there are currently no effective therapeutic interventions that improve brain outcomes following TBI. As a result, a number of experimental TBI models have been developed to recapitulate TBI injury mechanisms and to test the efficacy of potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 159 publications
0
37
0
Order By: Relevance
“…Along with rodent models, much work has been done to better identify similarities and caveats of other animal injury models. Notably, large animal models such as pigs may offer additional insight due to the similar size, organization, and development of the brain to humans (170). Lastly, continued emphasis must be placed on translation from pre-clinical to clinical work while maintaining an appreciation for species-specific differences.…”
Section: Future Steps In Pre-clinical and Clinical Trauma Researchmentioning
confidence: 99%
“…Along with rodent models, much work has been done to better identify similarities and caveats of other animal injury models. Notably, large animal models such as pigs may offer additional insight due to the similar size, organization, and development of the brain to humans (170). Lastly, continued emphasis must be placed on translation from pre-clinical to clinical work while maintaining an appreciation for species-specific differences.…”
Section: Future Steps In Pre-clinical and Clinical Trauma Researchmentioning
confidence: 99%
“…As such, using an animal model with a similar WM to GM ratio will be critical in understanding alcohol induced neuropathology ( Figure 2A ). The mature rat brain is comprised of < 12% of WM while the mature human and pig brains have > 60% ( Figure 1 ; Kinder et al, 2019 ). As alcohol exhibits differential damage on these tissues, having a similar WM to GM ratio would result in a similar pattern of injury on the brain and thus similar manifestation of deficits as a result of the injury.…”
Section: Discussion: a Translational Porcine Model Provides Potentialmentioning
confidence: 99%
“…We demonstrated that the combination of vessel diameter and RBC velocity to calculate RBC flux in individual vessels remained effective in a porcine model of traumatic brain injury. Cortical impact has been demonstrated to reproducibly impair autoregulation capacity as measured by pial arteriolar diameter and LDF changes 2830 .…”
Section: Discussionmentioning
confidence: 99%